PSYCHOMOTRICITY: INFLUENCE OF THE INTERVENTIONS IN THE INFANTILE MOTOR DEVELOPMENT (Fiep Bulletin - online, 2014)
The purpose of this study was to verify the influence of the psychomotor interventions in children with problems in the learning and children with syndroms (Down and Willians). The research is experimetal. Was utilized the tests of Motor Development Scale  EDM (ROSA NETO, 2002). The sample involved 30 children, age between 5 and 10 years, that participate of the Psychomotricity Program of  the Laboratory of Human Development in the CEFID/UDESC, being 19 children in 2º semester of 2005 and 11 in 1º semester of 2006. The related project promotes a program directed to the psychomotor stimulation and re-education to these children, through playful activities and stimulants, working the areas fine and global motricity, balance, corporal project, space, secular organization and laterality. The interventions had been carried through two times in the week, with duration of 50 minutes each, divided in two groups (morning and late), being that only the group of the morning had the participation of sindrômicas children. The joined results demonstrate advances in the diverse worked motor areas, in the two groups. Front to the return of the parents, perceived an immense and unanimous satisfaction of the same ones in relation to the Project and the general development of the children, either in the half pertaining to school, social or familiar.
Keywords: Motor development; Psychomotricity; Problems in the learning